Impact of adenomyosis on fertility and obstetric outcomes among women in tertiary care center - Hoque, Luna Farhana; Begum, Fatema; Apsara, Suraiya; Zinan, Aklima Zakaria (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Adenomyosis is a serious reproductive difficulty caused by aberrant endometrial tissue within the myometrium. It can induce infertility and predispose women to hypertensive problems, preeclampsia, and preterm birth. However, the influence of adenomyosis on fertility and obstetric outcomes has not been extensively explored, particularly in resource-limited settings. This study aimed to investigate the effect of adenomyosis on fertility and obstetric outcomes in women who visited a tertiary care hospital in Dhaka, Bangladesh. Methods: A case control study was conducted in Shahabuddin Medical College Hospital and one IVF center from June 2023 to May 2024. The study included 100 women divided into two groups: A case group of 50 with adenomyosis and 50 in the control group without. Two groups were compared in terms of baseline characteristics, fertility outcomes, obstetric complications, and delivery outcomes. SPSS software statistical analysis was performed. Results: Obstetric complications such as hypertensive disorders (32% versus 6%, p=0.001), preeclampsia (16% versus 2%, p=0.01) and preterm delivery (26% versus 8%, p=0.01) were more frequent in the adenomyosis group. The adenomyosis group also had a higher caesarean delivery rate (62% versus 34%), p<0.05. Outcomes in fertility, namely implantation rates and live birth rates were not different (p>0.05). Conclusions: Early diagnosis and careful management of adenomyosis are important because adenomyosis is associated with increased obstetric complications and higher caesarean delivery.